Nutrient status alters developmental fates via a switch in mitochondrial homeodynamics - Jie Zhang; Suning Liu; Yang Li; Guanfeng Xu; Huimin Deng; Kirst King-Jones; Sheng Li (Nature Communications)
Abstract Steroid hormones are powerful endocrine regulators, but little is known about how environmental conditions modulate steroidogenesis to reprogram developmental fates. Here, we use the Drosophila prothoracic gland (PG) to investigate how a nutrient restriction checkpoint (NRC) ensures or blocks developmental progression and sexual maturation via regulating steroidogenesis. Extensive transcriptome analysis of the PG reveals that pre-NRC starvation significantly downregulates mitochondria-associated genes. Pre-NRC starvation reduces prothoracicotropic neuropeptide hormone signaling, insulin signaling, and TORC1 activity in PG cells, which prevent mitochondrial fragmentation and import of Disembodied, a key steroidogenic enzyme. Ultimately, pre-NRC starvation causes severe mitophagy and proteasome dysfunction, blocking steroidogenesis and metamorphosis. By contrast, post-NRC starvation does not impair mitochondrial homeostasis in PG cells but reduces sit expression and induces moderate autophagy to promote steroidogenesis, leading to precocious metamorphosis. This study constitutes a paradigm for exploring how steroid hormone levels are controlled in response to environmental stress during developmental checkpoints.